2020
DOI: 10.1113/jp279741
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of synaptic activity‐induced astrocytic volume transient

Abstract: Neuronal activity causes astrocytic volume change via K + uptake through TREK-1 containing two-pore domain potassium channels. r The volume transient is terminated by Cl − efflux through the Ca 2+-activated anion channel BEST1. r The source of the Ca 2+ required to open BEST1 appears to be the stretch-activated TRPA1 channel. r Intense neuronal activity is synaptically coupled with a physical change in astrocytes via volume transients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 64 publications
(195 reference statements)
1
18
0
Order By: Relevance
“…We, therefore, compare and discuss the properties that make particular GECIs useful for particular applications, which should help in selecting from yet newer GECIs and not only from those in Figures 1, 2. In the figurative summaries, we have highlighted those references in which GECIs have been published in astrocytes (Atkin et al, 2009;Haustein et al, 2014;Kanemaru et al, 2014;Monai et al, 2016;Nakayama et al, 2016;Srinivasan et al, 2016;Stobart et al, 2018;Woo et al, 2020).…”
Section: A Field Guide To Gecis For Use In Glial Cellsmentioning
confidence: 99%
“…We, therefore, compare and discuss the properties that make particular GECIs useful for particular applications, which should help in selecting from yet newer GECIs and not only from those in Figures 1, 2. In the figurative summaries, we have highlighted those references in which GECIs have been published in astrocytes (Atkin et al, 2009;Haustein et al, 2014;Kanemaru et al, 2014;Monai et al, 2016;Nakayama et al, 2016;Srinivasan et al, 2016;Stobart et al, 2018;Woo et al, 2020).…”
Section: A Field Guide To Gecis For Use In Glial Cellsmentioning
confidence: 99%
“…Recently, we postulated that diffusion MRI can detect the astrocyte volume change because astrocytes undergo dramatic volume changes as a result of fluid flux associated with extracellular K + release and subsequent activation of the astrocyte Na–K–Cl cotransporter (NKCC1), Kir4.1 inwardly rectifying potassium channel, and/or the Na + /K + ATPase [ 168 , 169 , 170 , 171 , 172 , 173 ]. In addition, AQP4 activity may contribute to these volume changes by mediating ISF–CSF exchange [ 174 ].…”
Section: Potential Noninvasive and Mesoscopic Astrocyte Imaging Using Mri And Positron Emission Tomography (Pet)mentioning
confidence: 99%
“… 1 Suzuki and Mizuno, 2004 ; 2 Suzuki, 2006 ; 3 Sabirov and Okada, 2009 ; 4 Han et al, 2019 ; 5 Woo et al, 2020 . …”
Section: Structure and Biochemical Function Of Tweety Family Proteinsmentioning
confidence: 99%
“…All three murine Tweety paralogs display activity of swelling-dependent volume-regulated anion channels (VRAC swell ) in mouse astrocyte primary culture when assessed by whole-cell patch-clamp recording and shRNA-mediated knockdown diminished current (Han et al, 2019 ; Supplementary Table 1 ). Additionally, expression of each TTYH in HEK293T and CHO-K1 cells resulted in an I Cl, Swell similar to that of native astrocytes, and all three Tweety paralogs were shown to be involved in the regulated volume decrease through a VRAC current in hippocampal astrocytes (Han et al, 2019 ; Woo et al, 2020 ). Bae et al ( 2019 ) found that TTYH1 and TTYH2 are both responsible for generating VRAC currents in the SNU-601 gastric cancer cell line after using CRISPR-Cas9 technology to delete exon 7 of the TTYH1 gene and exons 2 and 3 of the TTYH2 gene, which reduced VRAC currents in the resulting knockout cells.…”
Section: Structure and Biochemical Function Of Tweety Family Proteinsmentioning
confidence: 99%